Analysis of The Influence of Socio-Economic Status and Demographics on Depression Symptoms in Marriage - Sibarani, Rachel Arielle; Larosa, Nina Ardya Putri; Tarani, Ni Putu Mia; Kautsar, Achmad (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2024)
More than 19 million people experience mental and emotional disorders, and more than 12 million people aged over 15 years’ experience depression in Indonesia, one of which is experienced in marriage. Symptoms of depression in a marriage are influenced by demographic and socio-economic status. This research aims to analyze the possibility of depressive symptoms occurring in marriage using several variables including income level, happiness, number of children, and education. This research uses a logit model to analyze the probability of an event. The number of observations used in the research was 2,685 using data from the Indonesian Family Life Survey 5. The results of the study showed that income level had a significant negative relationship of 30.3 percent to depression in marriage. Other factors such as education can also have an influence and satisfaction in the family also has a positive impact on the quality of marital relationships. From this research, results were obtained that show factors that influence depression in marriage to reduce the probability of experiencing depression in marriage.